The differences historical abortion and hemoglobin between hazard volcano eruption - Susanto, Nugroho; Hidayani, Wuri Ratna; Apriyan, Nur (Intelektual Pustaka Media Utama, 2024)
The disaster area volcano is priority for intervention through maternal health is vulnerable group. Previous study estimate severe bleeding /haemorrhage was up to 71.9%, anaemia 51%. The study aimed to know incident of history abortion and haemoglobin in zone hazard risk volcanic eruption after 10th. Study addressed with cross-sectional design. The data history abortion and haemoglobin were collected with medical record in Puskesmas Cangkringan. The hazard level adoption in National Disaster Management Agency/Badan Nasional Penanggulangan Bencana (BNPB) divide 3 zone hazard risks. Data analysis by Health Mapper version 4.3 software and analysis with analysis of variance (ANOVA). The incidence of history abortion higher in zone 2 compare zones 1 and 3 volcanic disaster. The average of haemoglobin higher in zone 1 as 12.54±1.67 compare zones 2 and 3 volcanic disaster. No significant differences history abortion and haemoglobin between zones 1 to 3 volcanic disaster. The study concluded that history of abortion higher in zone 3 compared zones 1 and 2 volcanic disaster. The average of haemoglobin higher in zone 1 compared zones 2 and 3 volcanic disaster. No differences significant of history abortion and average haemoglobin between zones 1 to 3.